Cultivating Future Nurse Leaders With Student Nurses Associations. Issue 4 (19th August 2013) - Akans, Merlana; Harrington, Maura; McCash, John; Childs, Ashlyn; Gripentrog, Jessica; Cole, Sharon; Fitzgerald, Kevin; Searing, Kimberly; Fuehr, Patricia
Abstract Student nurses associations (SNAs) assist in developing tomorrow's nurse leaders. In this article, executive board members of an SNA in a traditional baccalaureate nursing program at a public regional university recounted common themes in their participation in an SNA. These broad themes included leadership, mentorship and communication, all which foster professional development through the acquisition of specific knowledge, skills and experiences.